2022
DOI: 10.3389/fmicb.2022.797197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Wrinkled Variants Isolated From Pseudoalteromonas lipolytica Biofilms

Abstract: Many Pseudoalteromonas species are dominant biofilm-forming Gammaproteobacteria in the ocean. The formation of Pseudoalteromonas biofilms is often accompanied by the occurrence of variants with different colony morphologies that may exhibit increased marine antifouling or anticorrosion activities. However, the genetic basis of the occurrence of these variants remains largely unexplored. In this study, we identified that wrinkled variants of P. lipolytica mainly arose due to mutations in the AT00_08765, a wspF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Intriguingly, the Wsp chemotactic signalling pathway and the YfiBNR system are also major targets of mutational events leading to the development of small colony variants of P. aeruginosa upon colonization of the cystic fibrosis lung [ 150, 151 ] and in rhizosphere-colonizing Pseudomonas chlororaphis [ 152 ]. Similarly, mutations in the Wsp chemotactic pathway arise readily upon chronic infection in a full-thickness burn wound model [ 153 ], the challenge of P. aeruginosa with sub-lethal concentrations of hydrogen peroxide, the subjection of Burkholderia cenocepacia to a heterogeneous microcosm [ 154 ], other infections where hyper biofilm producers with elevated cyclic di-GMP levels are observed [ 155 ] and also upon biofilm formation of oceanic Pseudoalteromonas lipolytica [ 156 ]. An unexpected twist is a point mutation in the 5′ untranslated region of the fatty acid biosynthesis accBC gene cluster which might activate the Wsp signalling pathway by alteration of the fatty acid composition of the membrane [ 157 ].…”
Section: Variability In Model Systems Pseudomonas Fluor...mentioning
confidence: 99%
“…Intriguingly, the Wsp chemotactic signalling pathway and the YfiBNR system are also major targets of mutational events leading to the development of small colony variants of P. aeruginosa upon colonization of the cystic fibrosis lung [ 150, 151 ] and in rhizosphere-colonizing Pseudomonas chlororaphis [ 152 ]. Similarly, mutations in the Wsp chemotactic pathway arise readily upon chronic infection in a full-thickness burn wound model [ 153 ], the challenge of P. aeruginosa with sub-lethal concentrations of hydrogen peroxide, the subjection of Burkholderia cenocepacia to a heterogeneous microcosm [ 154 ], other infections where hyper biofilm producers with elevated cyclic di-GMP levels are observed [ 155 ] and also upon biofilm formation of oceanic Pseudoalteromonas lipolytica [ 156 ]. An unexpected twist is a point mutation in the 5′ untranslated region of the fatty acid biosynthesis accBC gene cluster which might activate the Wsp signalling pathway by alteration of the fatty acid composition of the membrane [ 157 ].…”
Section: Variability In Model Systems Pseudomonas Fluor...mentioning
confidence: 99%
“…We previously also found that wrinkled variants isolated from P. lipolytica biofilms harbour spontaneous mutations in the flagellar regulatory gene wspF or flagellar biosynthesis gene flhA , leading to a reduction in swimming activity [21, 25]. However, there is still limited knowledge linking reduced swimming motility to the specific hot mutation targets introduced by the mutS deletion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during long-term colonization in adult mice, spontaneous nonmotile variants of V. cholerae were highly produced at a rate of approximately 10 %, in which the mutations occurred primarily in conserved regions of the flagellar regulatory genes flrA and flrC [40]. We previously also found that wrinkled variants isolated from P. lipolytica biofilms harbour spontaneous mutations in the flagellar regulatory gene wspF or flagellar biosynthesis gene flhA, leading to a reduction in swimming activity [21,25]. However, there is still limited knowledge linking reduced swimming motility to the specific hot mutation targets introduced by the mutS deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bio lm is a special matrix of bacteria that live as a community in close contact enabling several advantages like cell to cell communication, digestion of nutrients and protection for vital activities including growth, reproduction, and functional activity in the marine environment (Drescher et al 2014; Zeng et al 2022). The microbial cells inside the bio lm structure are supported by the secretion of extracellular enzymes and polymeric substances to digest and take nutrients, respectively, from the marine environment (Flemming and Wingender 2010).…”
Section: Introductionmentioning
confidence: 99%